Cover Feature: Understanding the Uniqueness of 2p Elements in Periodic Tables (Chem. Eur. J. 67/2020). Issue 67 (18th November 2020) - Wang, Zhen‐Ling; Hu, Han‐Shi; von Szentpály, László; Stoll, Hermann; Fritzsche, Stephan; Pyykkö, Pekka; Schwarz, W. H. Eugen; Li, Jun
Abstract : The 2p elements exhibit chemistries qualitatively different from their heavier congeners. The physical origin is the quantitative interplay of electronic, kinetic, and potential energies: The 2p orbital has no radial node and therefore little radial kinetic energy, thus 2p is radially rather contracted. All n s orbitals are weakly shielded from nuclear attraction in many‐electronic atoms, thus all n s‐orbitals are radially contracted. Therefore r2s /r2p ≈1 for n =2 supporting sp‐hybridization, but r n s /r n p <1 for n >2. More information can be found in the Full Paper by P. Pyykkö, W. H. E. Schwarz, J. Li, et al. on page 15558 .